I3 = Let us Talk less and Practice it More - Deshpande, Nitin (Journal of Engineering Education Transformations, 1995)
Present Scenario - Institutional : If we consider Institution as a manufacturing / processing unit, then the product (Le . the student) gets processed from RAW to FINAL in three basic phases .. The first is the Designing phase. Th.ls IS attended to, by universities, eminent educationists and various academic bodies.